Pendidikan Agama Kristen Sebagai Upaya Pencegahan Perilaku Menyimpang pada Remaja - Nofita R. Asbanu; Claudina M. Freitas Belo; Salomi Poko; Andrian W. Syahputra (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study discusses the role of Christian Religious Education (PAK) in preventing deviant behavior in adolescents. Adolescence is a critical phase marked by changes in identity and environmental influences. Without proper guidance, adolescents are vulnerable to deviant behavior such as brawls, drug abuse, and free sex. With the increasing use of social media, ethical values ​​are often neglected, so relevant education becomes very important. Through a contextual approach, PAK is expected to shape the character and morals of adolescents. However, the effectiveness of PAK is often hampered by rigid teaching methods and a lack of collaboration between families, schools, and churches. This study uses a descriptive qualitative method with literature analysis to explore the challenges and opportunities in implementing PAK. The results show that PAK has great potential in shaping the character of adolescents, but requires innovation and synergy from all related parties. Collaboration between families, schools, and churches is important to create an environment that supports the spiritual and moral growth of adolescents.